First report of established mite populations, Tropilaelaps mercedesae, in Europe - Brandorf, Anna; Ivoilova, Marija M.; Yañez, Orlando; Neumann, Peter; Soroker, Victoria (Journal of apicultural research, 2025)
Ectoparasitic mites Tropilaelaps spp. (Mesostigmata: Laelapidae) can be devastating pests of Western honey bee, Apis mellifera L., colonies, but have so far occurred only in Asia. Here, we report for the first time on established populations in Europe. In 2021, high losses of honey bee colonies occurred in the Krasnodar region, Western Russia (53%) with clinical symptoms and mite morphology showing Tropilaelaps spp. infestations. We found that brood infestations fluctuated seasonally, and mites were able to overwinter locally. The specimens were identified as Tropilaelaps mercedesae using genetics. The source of pest invasion is yet unidentified, but it is very likely that T. mercedesae will further spread west and south. This calls for respective stakeholder action, especially in neighboring countries.